Temperature insensitive long-period grating sensors in photonic crystal fibre - Kalli, Kyriacos; Dobb, Helen L.; Webb, David J. (My University, 2004)
Presented are long-period gratings (LPGs) fabricated in pure silica photonic crystal fibre (PCF) using an electric arc. Two different varieties of PCF have been investigated, an endlessly single mode PCF and a large-mode area PCF. The LPGs have been characterised for their sensitivity to a variety of external measurands. The LPGs in both fibres have been found to have negligible temperature sensitivity whilst exhibiting good sensitivity to bending and strain.
Keywords: Diffraction gratings; Photons; Refractive index; Crystal whiskers